2011
DOI: 10.1508/cytologia.76.279
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological Study of Trigonella disperma (Fabaceae) in Iran

Abstract: Summary Chromosome number, meiotic behaviour and morphological characters related to habit and pollen grains were studied in 8 populations of Trigonella disperma of Trigonella sect. Ellipticae native to Iran. All populations are diploid and possess a chromosome number of 2n=2x=16, which is consistent with the proposed base number of x=8. This taxon displayed regular bivalent pairing and chromosome segregation at meiosis. However, some meiotic abnormalities observed included varied degrees of sticky chromosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Thus tri-polarity and disturbed polarity could be found due to un-oriented spindle apparatus which may lead to producing unbalanced and sterile gametes. Moreover, failure of chromosome movement occurred in one of the poles of anaphase cells, leading to the formation of tri-polar cells (Ranjbar et al 2011). Chromosome breakage and vagrant chromosome (Grewal and Rani 2019) might be due to the clumping of chromosomes and clumping might occur as a consequence of the stickiness of chromosomes in this present study.…”
Section: Meiotic Abnormalitymentioning
confidence: 51%
See 1 more Smart Citation
“…Thus tri-polarity and disturbed polarity could be found due to un-oriented spindle apparatus which may lead to producing unbalanced and sterile gametes. Moreover, failure of chromosome movement occurred in one of the poles of anaphase cells, leading to the formation of tri-polar cells (Ranjbar et al 2011). Chromosome breakage and vagrant chromosome (Grewal and Rani 2019) might be due to the clumping of chromosomes and clumping might occur as a consequence of the stickiness of chromosomes in this present study.…”
Section: Meiotic Abnormalitymentioning
confidence: 51%
“…Meiotic abnormalities or irregularities observed at meiosis probably have a direct relation with pollen fertility (Ranjbar et al 2011). In the present investigation, the pollen fertility of BARI Methi-1, BARI Methi-2, BARI Methi-3, and BARI Firingi-1 was more than 95% though these specimens exhibited several kinds of meiotic abnormalities (Table 5).…”
Section: Effect Of B Chromosomes On Chiasma Frequency Andmentioning
confidence: 99%
“…The results of our cytogenetic study showed that the basic chromosome number of x = 8 for the new species is equal to that of all species of T. sect. Ellipticae (Hesamzadeh & Ziaei-Nasab 2009;Ranjbar et al 2011aRanjbar et al , 2012b. Hence, the diploid state has been retained during speciation within this perennial section.…”
Section: Discussionmentioning
confidence: 99%
“…H, J, D). Desynapsis is considered as the precocious separation of bivalents in metaphase of meiosis I, leading to formation of various numbers of univalents (Ranjbar et al , ). Desynapsis was found only in 2.5% of D/MI cells (Fig.…”
Section: Methodsmentioning
confidence: 99%